Blurred vision and high blood pressure in a young woman. Issue 876 (October 1998) - Flanagan, D. E.; Cole, C.; Crick, M. D.; Kerr, D.
Abstract : A 41-year-old woman presented with a short history of blurred vision. She had a 6-year history of refractory hypertension which had been treated with a variety of drug regimens. She was found to have bilateral branch retinal vein occlusion. Retinal vein occlusion is a recognised complication of hypertension but simultaneous involvement of both eyes is extremely rare. Following this episode, blood pressure control has improved without change in drug therapy, suggesting that treatment compliance may partly explain the previous difficulties.